How to Teach the Basic Concept of Function in Senior High School: a Lesson Study - Yalei Shao; Ying Zhou; Tommy Tanu Wijaya; Lijuan Gan (Edumatika, 2021)
Teaching methods are a complex topic in mathematics education. This study aims to analyze the teaching methods of previous relevant studies and design a new lesson study on how to teach the topic of functions at the high school level in China. Lesson study focuses on the basic concepts of function and problem-solving abilities. The researcher uses the research and development method to teach the material function at the high school level. This Lesson Study is used to teach in China. The researcher explains 4 important aspects in designing a lesson study, namely the introduction or opening section, the instructional section or core section, the assessment section, and the closing section.